"Frank Davey" and the Method of Cool - Kamboureli, Smaro (Studies in Canadian Literature, 2007)
"Frank Davey" is an important cultural institution in the context of Canadian literature and criticism. The complexity of his work reveals his preoccupation with the various institutional exigencies and cultural materiality of literary production, thus functioning at once as a politics and a poetics. Davey's work is a serial critical text about power, literariness, and the exigencies of the Canadian nation-state, and his canonical essay "Surviving the Paraphrase" (1978) illustrates the internal contradictions in his anti-thematic approach. Yet, the self-reflexivity that characterizes Davey's critical practice in such works as Reading Canadian Reading (1988) shows him to be concerned with the historiography and errancy of his own critical discourse: the critic is, then, a writerly text, a text that can be re-read, re-vised, chastised.